Ensuring Security and Compliance in Agile Cloud Infrastructure Projects - Suvvari, Sunil Kumar (International Journal of Computing and Engineering, 2024)
Purpose: This research paper investigates strategies for ensuring security and compliance in agile cloud infrastructure projects. Methodology: The study synthesizes current literature, industry reports, and expert insights to provide a comprehensive overview of the topic. Findings: Key challenges identified include rapid deployment cycles, shared responsibility models, and data sovereignty concerns. The research proposes strategies such as shift-left security approaches, continuous compliance monitoring, and automated security testing. The importance of organizational culture shifts and the evolving role of cloud service providers in shared security responsibilities are highlighted. Unique Contribution to Theory, Policy and Practice: The paper offers recommendations for practitioners navigating the complex landscape of security and compliance in agile cloud projects. It provides insights into integrating security and compliance into agile methodologies, leveraging cloud-native security tools, and the potential impact of AI and machine learning on cloud security.